World-Class Universities: Lessons for Slovenia - Altbach, Philip (International Higher Education, 2012)
Slovenian universities are arguably the best in the central Europe. Slovenia's higher education contextand as- pirationshas relevance not only for other countries with small populations but also for universities with a traditional continental European pattern of academic governance and administration.